2008
DOI: 10.1016/j.molcel.2008.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Mammalian Sin3 in Permanent Gene Silencing

Abstract: Summary The multi-subunit Sin3 co-repressor complex regulates gene transcription through deacetylation of nucleosomes. However, the full range of Sin3 activities and targets is not well understood. Here, we have investigated genome-wide binding of mouse Sin3 and RBP2 as well as histone modifications and nucleosome positioning as a function of myogenic differentiation. Remarkably, we find that Sin3 complexes spread immediately downstream of the transcription start site on repressed and transcribed genes during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
132
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 37 publications
17
132
1
Order By: Relevance
“…Although Rb1 classically represses genes in a cell cycle-dependent fashion to regulate proliferation, a number of other genes have been shown to be constitutively repressed by Rb1 in proliferating cells. Such genes include proapoptotic factors as well as cdk inhibitors (43). It has been suggested that release of constitutive repression of such genes can serve a tumor suppressor function that inhibits viability when the Rb1 pathway is lost.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rb1 classically represses genes in a cell cycle-dependent fashion to regulate proliferation, a number of other genes have been shown to be constitutively repressed by Rb1 in proliferating cells. Such genes include proapoptotic factors as well as cdk inhibitors (43). It has been suggested that release of constitutive repression of such genes can serve a tumor suppressor function that inhibits viability when the Rb1 pathway is lost.…”
Section: Discussionmentioning
confidence: 99%
“…This region is subject to imprinting (40), the maternal-or paternal-specific silencing of gene expression through histone deacetylation and DNA methylation. Considering the potential regulatory networks formed by histone H3 deacetylation and DNA methylation (41), permanent gene silencing by HDAC activity during differentiation (42), and microRNA feedback control of the Dlk1-Dio3 region genes (38), further investigation of HDACi influence on pluripotency will certainly include work to identify the regulatory mechanisms operating at this chromosomal region. Indeed, an iPS cell line silenced at Dlk1-Dio3 showed reactivation of the region's genes upon HDACi treatment, which then conferred full pluripotency and development to all-iPS mice (39).…”
Section: Discussionmentioning
confidence: 99%
“…Stephan and Koch (2009) found that Sin3 and HDAC Rpd3 were both recruited to promoters of SBF (Swi4/Swi6)-regulated genes (CLN1, CLN2, and PCL1) in yeast. van Oevelen et al (2008van Oevelen et al ( , 2010 showed by ChIP assay that SIN3 directly impacts acetylation levels downstream of the transcriptional start site of target genes in mouse. Although ChIP assays for direct interaction between SNL1 and ethylene/ABA genes did not function in our hands, we speculate that the differentially expressed genes with altered histone acetylation level in the snl1 snl2 mutant could be the target genes of SNL1 or SNL2.…”
Section: Snl1 and Snl2 Regulate Gene Transcription Through Histone Dementioning
confidence: 99%